1996
DOI: 10.1016/0167-4889(96)00098-5
|View full text |Cite
|
Sign up to set email alerts
|

S-100 (α and β) binding peptide (TRTK-12) blocks S-100/GFAP interaction: identification of a putative S-100 target epitope within the head domain of GFAP

Abstract: Alignment of previously characterized S-100 (alpha and beta)-binding peptides (J. Biol. Chem. 270, 14651-14658) has enabled the identification of a putative S-100 target epitope within the head domain of glial fibrillary acidic protein (GFAP). The capacity of a known peptide inhibitor of S-100 protein (TRTK-12), homologous to this region, to perturb the interaction of S-100 (alpha and beta) and GFAP (J. Biol. Chem 268, 12669-12674) was investigated. Fluorescence spectrophotometry and chemical cross-linking ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 55 publications
2
31
0
Order By: Relevance
“…It is intriguing that secondary structure prediction methods show that TRTK-12 should form an amphipathic ␣-helix between residues Lys 4 and Leu 11 . If this structure exists in the S100B-protein complex, it would place residues Thr , and Ile 11 on one side of the helix, allowing integral contact of Leu 10 and Ile 11 with S100B. On the surface, this would provide differences between the interactions of TRTK-12 with Ca 2ϩ -S100B compared with p53.…”
Section: Zn 2ϩ Enhancement Of Trtk-12 Binding To S100bmentioning
confidence: 99%
See 1 more Smart Citation
“…It is intriguing that secondary structure prediction methods show that TRTK-12 should form an amphipathic ␣-helix between residues Lys 4 and Leu 11 . If this structure exists in the S100B-protein complex, it would place residues Thr , and Ile 11 on one side of the helix, allowing integral contact of Leu 10 and Ile 11 with S100B. On the surface, this would provide differences between the interactions of TRTK-12 with Ca 2ϩ -S100B compared with p53.…”
Section: Zn 2ϩ Enhancement Of Trtk-12 Binding To S100bmentioning
confidence: 99%
“…These studies showed that a 12-residue sequence containing the consensus motif (K/R)(L/ I)XWXXIL was sufficient to bind to S100B in a calcium-sensitive manner. Further studies have shown this peptide (TRTK-12) successfully competes with other proteins such as glial fibrillary acidic protein and CapZ for calcium-sensitive S100B binding (10,18). Similar approaches have identified several 15-residue sequences, analogous to the sequences for myosin light chain kinase, melittin, and mastoparan, as representative samples of the calcium-dependent target proteins for calmodulin (19).…”
mentioning
confidence: 99%
“…CapZ for calcium-sensitive S100B binding (Ivanenkov et al, 1995;Bianchi et al, 1996). This consensus sequence for S100B binding has been identified in 25 proteins found to interact in vitro with S100B (McClintock and Shaw, 2000).…”
Section: Identification Of D 2 Receptor-binding Proteins Bymentioning
confidence: 99%
“…A putative S100B-binding motif is located near the N terminus of the third intracellular loop of the D 2 receptor. The amino acid sequence for the rat D 2 receptor was analyzed based on the previous reports (Ivanenkov et al, 1995;Bianchi et al, 1996;McClintock and Shaw, 2000). A putative S100B binding motif close to the N terminus (amino acids: 233-240) of the third intracellular loop of the D 2 receptor is aligned with TRTK-12 peptide characterized by Ivanenkov et al (1995).…”
Section: Identification Of D 2 Receptor-binding Proteins Bymentioning
confidence: 99%
“…Several lines of evidence suggest that S100B and S100A1 interact with the Nterminal head of both GFAP and desmin, thereby sequestering unassembled subunits and blocking the head-to-tail association of subunits into IF polymers (53,(56)(57)(58) (Figure 3). 1) Neither headless GFAP or desmin nor headless/tailless GFAP or desmin (i.e., their rod domain) as obtained by enzymatic cleavage was able to interact with either S100 protein.…”
Section: S100b and S100a1 Regulate The Dynamics Of Intermediate Filammentioning
confidence: 99%